A Combined Adjuvant TF–Al Consisting of TFPR1 and Aluminum Hydroxide Augments Strong Humoral and Cellular Immune Responses in Both C57BL/6 and BALB/c Mice - Qiao Li; Zhihua Liu; Yi Liu; Chen Liang; Jiayi Shu; Xia Jin; Chuanyou Li; Zhihua Kou (Vaccines, 2021)
TFPR1 is a novel adjuvant for protein and peptide antigens, which has been demonstrated in BALB/c mice in our previous studies; however, its adjuvanticity in mice with different genetic backgrounds remains unknown, and its adjuvanticity needs to be improved to fit the requirements for various vaccines. In this study, we first compared the adjuvanticity of TFPR1 in two commonly used inbred mouse strains, BALB/c and C57BL/6 mice, in vitro and in vivo, and demonstrated that TFPR1 activated TLR2 to exert its immune activity in vivo. Next, to prove the feasibility of TFPR1 acting as a major component of combined adjuvants, we prepared a combined adjuvant, TF–Al, by formulating TFPR1 and alum at a certain ratio and compared its adjuvanticity with that of TFPR1 and alum alone using OVA and recombinant HBsAg as model antigens in both BALB/c and C57BL/6 mice. Results showed that TFPR1 acts as an effective vaccine adjuvant in both BALB/c mice and C57BL/6 mice, and further demonstrated the role of TLR2 in the adjuvanticity of TFPR1 in vivo. In addition, we obtained a novel combined adjuvant, TF–Al, based on TFPR1, which can augment antibody and cellular immune responses in mice with different genetic backgrounds, suggesting its promise for vaccine development in the future.